Unilateral pseudouveitis revealing a pancreatic neuroendocrine carcinoma: A case report. Issue 3 (8th March 2022) - Cherchir, Faten; Naceur, Ines; Haouari, Ahmed Anas; Ben Achour, Tayssir; Ben Mansour, Hajer; Bellil, Khadija; Said, Fatma; Houman, Mohamed Habib
Abstract: Neuroendocrine tumors are a heterogeneous group of tumors with a wide range of malignant potential that tend to have a relative prolonged course. These tumors infrequently metastasize to the orbit. To the best of our knowledge, ocular metastases from pancreatic neuroendocrine tumors (PNETs) have never been reported in the literature. We report the case of a 61‐year‐old man who presented with progressive deterioration of general condition with unilateral recurrent episodes of non‐granulomatous panuveitis of the left eye related to a choroidal metastasis. Radiological imaging and histopathological analyses led to the diagnosis of metastatic pancreatic neuroendocrine carcinoma as the primary tumor. Choroidal metastases from neuroendocrine tumors are extremely rare, but compromise patients' well‐being because of visual impairment. Uncommonly, these metastases can be the first manifestation of unknown tumors, warranting further investigations to detect the primary cancer. Abstract : We report the case of a 61‐year‐old man with unilateral recurrent panuveitis related to choroidal metastasis. Explorations led to the diagnosis of pancreatic neuroendocrine carcinoma as the primary tumor. Choroidal metastases from neuroendocrine tumors are extremely rare. Uncommonly, these metastases can be the first manifestation of unknown tumors.